SEKA DALAM KONTEKS KEHIDUPAN MASYARAKAT DAN KESENIAN BALI - I Gusti Gede Putra (Institut Seni Indonesia Surakarta, 2009)
This article focuses on Seka in the context of Balinese art and social life. Seka is a professional organization of which the scope is smaller than a traditional organization in Bali, like banjar and village. Seka is a smaller part but it covers certain parts of banjar and village. This article aims to describe the form and role and Seka in the context of Balinese art and social life. The results of the analysis show that Seka is a social group of which the members have close relation, which has a special feature and goal, and which uses direct and indirect patterns of communication. Seka is engaged in art, social and economic life, customs, religion and hobby. It has a great role in religious life, especially Seka which is engaged in art. The members of this kind of Seka do not hope for payment when they give a hand in carrying out customary rituals. In case of tourism, Seka participates in making an effort to attract tourists. Seka charges a fee for this affair to increase the welfare of the members.Keyword : seka